Register, Source Language, and Cognateness Effects on Lexical Choice in Translated Dutch - Vandevoorde, Lore (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2018)
In line with recent studies about register and source language effects on translated language (Delaere, De Sutter, et al. 2012; De Sutter, Delaere, et al. 2012; Kruger and Van Rooy 2012; Delaere and De Sutter 2017), the aim of this paper is twofold: to further investigate the influence of register and source language, and to study any potential influence of the variable “cognateness” on translated language. We focus on specific onomasiological choices (lexical choices) in the semantic field of inchoativity, made by translators into Dutch and attested in corpus observations (Dutch translated texts in the Dutch Parallel Corpus). First, we performed a multinomial regression analysis on our dataset and carried out an Analysis of Deviance to determine whether the predictor variables “source language lexeme” and “register” (“text type”) have a significant influence on the response variable (the set of lexemes representing the onomasiological choice range in translated Dutch inchoativity). Doing a second multinomial regression analysis, followed by an Analysis of Deviance, we investigate the influence of the new variable “cognateness” on the translator’s onomasiological choice (in the target language). Classification trees were generated as statistics-based visualizations of onomasiological choice in translated Dutch (translated from French and translated from English) within the semantic field of inchoativity. The results of the statistical analyses show that register, source language, and cognateness significantly influence the specific lexical choices made by translators. In addition, the visualizations show how the onomasiological choice for some target lexemes can be predicted on the basis of a single source language lexeme, while other choices are more complex, and will also be determined by the register of the text.